Place of Worship as Capital Space: The Relationship between Masjid Raya Bandung and Shopping Centers - Yuris Fahman Zaidan; Aquarini Priyatna; R. M. Mulyadi (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2020)
The mosque is generally known as a place of worship for Muslims.  Besides being seen as a physical and spiritual space, a mosque is also a cultural space.  The culture is manifested through the everyday life of people who are connected to the mosque.  The economy is part of the everyday life that will connect the mosque with other economic sectors such as shopping centers.  This research will show the relationship between the mosque and shopping centers that contribute to the development or production of capital space in the city.  Masjid Raya Bandung (MRB) is the focus of research to uncover the formation of capital space and its relationship with shopping centers around the MRB.  The method used is observation and in-depth interviews with people visiting the mosque and shopping centers.  The theory used to look at this case is the production of space from Henri Lefebvre.  The results showed that the mosque was not only seen as a place of worship, but also a capital space.  The formation of this capital space can be seen from the relation of MRB with the shopping places around it and the relations of the activities of visitors who presuppose these two spaces: the mosque and the shopping centers.  That way, the mosque is used as a means of perpetuating the economic process or consumerism in the surrounding spaces, including in shopping centers.